2015
DOI: 10.1186/s13018-015-0228-2
|View full text |Cite
|
Sign up to set email alerts
|

Changes over time in callus formation caused by intermittently administering PTH in rabbit distraction osteogenesis models

Abstract: BackgroundChanges over time in the callus during intermittent administration of parathyroid hormone (PTH) were studied in rabbit distraction osteogenesis models.MethodModels of distraction osteogenesis in Japanese white rabbits were created, and distraction osteogenesis (total length: 10.5 mm) was performed for 2 weeks. Simultaneously with the start of distraction, 30 rabbits received 4 weeks of subcutaneous administration of 30 μg/kg of PTH(1–34), teriparatide, (P-group: n = 15) or saline (N-group: n = 15) ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…In recent years, systemic treatment by the administration of rhPTH at daily intervals has been shown to improve bone healing in calvarial defects in rats,14, 15 implants placed in the tibia,4, 16 periodontal defects, 17 and distraction osteogenesis in rabbits 18, 19. However, the effects of local administration of rhPTH have not been completely evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, systemic treatment by the administration of rhPTH at daily intervals has been shown to improve bone healing in calvarial defects in rats,14, 15 implants placed in the tibia,4, 16 periodontal defects, 17 and distraction osteogenesis in rabbits 18, 19. However, the effects of local administration of rhPTH have not been completely evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…PTH is a polypeptide hormone consisting of 84 amino acids and exerts its biological effect via the 1-34 segment on the N-terminus region. This functional segment, known as rhPTH, has been shown to increase total bone mass by accelerating bone formation 18 . Systemic administration of rhPTH at daily intervals on spongy bone is thought to improve and strengthen the bone microstructure; it has been shown to exert this effect by increasing the connection between cortical and spongy bone and changing the structure of the trabeculae from a rod-like to a plate-like form 23 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data on the osteoanabolic effects of intermittent PTH in animal studies are accumulating [ 4 ]. When reviewing studies limited to rabbits, most studies have found positive effects of intermittent PTH on implant osteogenesis [ 11 , 31 , 34 ] and distraction osteogenesis [ 18 , 35 ]. A search for studies involving other animals and other sites did not reveal results of intermittent PTH administration not enhancing bone healing.…”
Section: Discussionmentioning
confidence: 99%
“…The early trials involved spinal fusion surgery, with PTH showing positive effects on the survival of allografts and autografts [ 15 17 ]. In other animal studies, PTH stimulated distraction osteogenesis in rabbits [ 18 ] and allograft integration in calvarial bone defects in mice [ 19 ]. Animal studies related to dental effects found that PTH stimulated healing after bone graft on extraction sockets [ 20 ] and calvarial bone autografts on the mandible in rats [ 21 ].…”
Section: Introductionmentioning
confidence: 99%